Schuelkelia gen. n., a new eastern Palaearctic ant-like stone beetle, with synopsis of Eurasian genera of Cyrtoscydmini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Schuelkelia unicornis gen. & sp. n. is described from Yunnan, China. The new taxon belongs to a group of genera characterized by the submentum lacking lateral sutures, and is most similar to Euconnus. Among the Eurasian genera Schuelkelia can be easily identified on the basis of the broad occipital constriction, pronotum lacking antebasal pits or grooves, elytra lacking externally visible basal foveae; mesoscutellum not visible between elytral bases; long and slender but weakly elevated mesoventral intercoxal process, and other features which are described and illustrated in detail. Morphological structures of Schuelkelia are compared with those of all other Palaearctic and Oriental Cyrtoscydmini, and keys to identification of all Eurasian and separately Chinese genera of Cyrtoscydmini are given. A brief illustrated synopsis of all genera of Cyrtoscydmini known to occur in the Oriental and Palaearctic regions is given, to facilitate identifications and future studies.